X-Ways Forensics practitioner's guide - Shavers, Brett (Syngress, is an imprint of Elsevier, 2014)
The X-Ways Forensics Practitioner's Guide is more than a manual-it's a complete reference guide to the full use of one of the most powerful forensic applications available, software that is used by a wide array of law enforcement agencies and private forensic examiners on a daily basis. In the X-Ways Forensics Practitioner's Guide, the authors provide you with complete coverage of this powerful tool, walking you through configuration and X-Ways fundamentals, and then moving through case flow, creating and importing hash databases, digging into OS artifacts, and conducting searches. With X-Ways Forensics Practitioner's Guide, you will be able to use X-Ways Forensics to its fullest potential without any additional training. The book takes you from installation to the most advanced features of the software. Once you are familiar with the basic components of X-Ways, the authors demonstrate never-before-documented features using real life examples and information on how to present investigation results. The book culminates with chapters on reporting, triage and preview methods, as well as electronic discovery and cool X-Ways apps. Provides detailed explanations of the complete forensic investigation processe using X-Ways Forensics. Goes beyond the basics: hands-on case demonstrations of never-before-documented features of X-Ways. Provides the best resource of hands-on information to use X-Ways Forensics.